THE USE OF FLASHCARD TO TEACH SPEAKING AT STUDENTS OF SMAN 12 MAKASSAR (Karya Ilmiah Mahasiswa (KIMA), 2022)
This research was discussed about The Use of Flashcard to Teach Speaking at The Students of SMA Negeri 12 Makassar. The aim of this research is to find out whether or not flashcard was effective to teach speaking english. The method that used was qualitative method. This research selected participants from students of SMAN 12 Makassar in 2021/2022 academic year. The sample consisted of 14 students, students from XI MIPA 1. This research used two kinds of instruments, namely observation and interview. The results of this study found that the use of flashcards could help students to improve their speaking skill. Most of the students of SMAN 12 Makassar were interested learning english by using the flashcard method, it also helped students to make conversation well and pronounced words or sentences fluently. On the other hand, this strategy was effective in teaching students to speak in classroom. Based on the results of observations there were several students who had problems such as 8 students were lack of confidence, 6 students with pronunciation, and 8 students were lack of vocabulary, and based on the results of the interview 12 of 14 students agreed that the flashcard method could improve speaking skill.